Sintered bearing and method for manufacturing sintered bearing
By removing the alumina coating from the core of the aluminum-bronze-based sintered bearing and managing the concentration of aluminum fluoride gas in the closed space, the problem of the strength of the sintered bearings during compaction is solved, and a combination of high mechanical strength and corrosion resistance is achieved.
Patent Information
- Application Number
- CN202080041392.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-02
- Filing Date
- 2020-06-17
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2040-06-17
AI Technical Summary
During the compaction process of aluminum-bronze-based sintered bearings, the strength will decrease beyond expectations, resulting in unstable mechanical properties.
By removing the alumina coating at the intergranular grain boundary at the core of the sintered bearing, and managing the concentration of aluminum fluoride gas in the enclosed space, a radial compressive strength of 200 MPa or more is ensured.
It realizes that while maintaining high corrosion resistance and mechanical strength, ensuring that the compactness of the sintered bearing does not affect its strength, and is suitable for high-demand mechanical parts.
Smart Images

Figure CN113906227B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a sintered bearing and a method for manufacturing the sintered bearing. Background Art
[0002] As a sintered bearing with excellent corrosion resistance, the aluminum bronze-based sintered bearing described in the following Patent Document 1 is well known. In the aluminum bronze-based sintered bearing, aluminum-copper alloy powder is mainly used as the raw material powder, but when the powder is sintered, there is a problem that the aluminum oxide (Al2O3) film formed on the particle surface during sintering significantly hinders sintering.
[0003] In order to solve this problem, aluminum fluoride is added to the raw material powder as a sintering aid in the sintered bearing described in Patent Document 1. According to the document, aluminum fluoride melts and slowly evaporates during the sintering of aluminum-copper alloy powder, thereby promoting sintering and increasing the diffusion of aluminum by protecting the surface of the aluminum-copper alloy powder and inhibiting the formation of aluminum oxide.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2013 / 137347 Summary of the invention
[0007] Technical problem to be solved by the invention
[0008] The aluminum bronze sintered bearings are used in, for example, fuel pumps for automobile engines. In recent years, as the demand for engine miniaturization and lightness has increased, the fuel pumps have also been required to be miniaturized and lightened, and the sintered bearings assembled into the fuel pumps have also been required to be compact (smaller in diameter or thinner in wall thickness, or both).
[0009] However, it is known that when an aluminum bronze sintered bearing is made compact, its strength decreases more than expected. The reason for this is unknown, and there is a strong demand for finding the cause of this problem and solving the problem.
[0010] Here, an object of the present invention is to stably ensure the strength of an aluminum bronze-based sintered bearing.
[0011] Solutions to technical problems
[0012] In order to solve this problem, the present invention is a sintered bearing, which is composed of a sintered body and has a structure obtained by sintering an aluminum-copper alloy, containing 3 to 13% by mass of aluminum and 0.05 to 0.6% by mass of phosphorus, the remainder of which is mainly copper and contains unavoidable impurities, and is characterized in that the aluminum oxide coating on the grain boundaries of the core is removed and has a radial compressive strength of more than 200 MPa.
[0013] As the sintered bearing, a sintered bearing having a hardness of HRF30 or more is preferable.
[0014] In addition, the preferred density is 5.6 g / cm 3 Above, 6.2g / cm 3 The following sintered bearings.
[0015] The sintered bearing further comprises free graphite.
[0016] In addition, the present invention is a method for manufacturing a sintered bearing, wherein the sintered bearing is formed by sintering a raw material powder containing aluminum fluoride, has a structure obtained by sintering an aluminum-copper alloy, contains 3 to 13% by mass of aluminum and 0.05 to 0.6% by mass of phosphorus, and the main component of the remainder is copper, and contains inevitable impurities, wherein the manufacturing method is characterized in that:
[0017] The sintering is performed in a closed space, and the sintering is performed while controlling the concentration of the aluminum fluoride gas assuming that all the aluminum fluoride contained in the raw material powder is vaporized in the closed space.
[0018] In this case, it is preferred that the sintering be performed while controlling the concentration of the aluminum fluoride gas to be 5 ppm or more.
[0019] In the manufacturing method, preferably, two or more powder compacts are arranged in the closed space, and the sintering is performed so that the ratio of the total volume of the two or more powder compacts to the volume of the closed space is 5% or more.
[0020] Furthermore, the closed space is preferably formed by a container body capable of accommodating two or more powder compacts and a cover detachable from the container body.
[0021] Furthermore, it is preferred that the raw material powder contain 0.05 to 0.3 mass % of aluminum fluoride.
[0022] Effects of the Invention
[0023] According to the present invention, a sintered bearing having high corrosion resistance and high mechanical strength can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a cross-sectional view showing a sintered bearing.
[0025] Figure 2 is a cross-sectional view showing a sintering furnace.
[0026] Figure 3A It is a top view of the container.
[0027] Figure 3B is along Figure 3ACross-sectional view along line DD.
[0028] Figure 4A Is the enlarged display Figure 1 Schematic diagram of the microstructure in part A.
[0029] Figure 4B Is the enlarged display Figure 1 Schematic diagram of the microstructure in part B.
[0030] Figure 4C It is a magnified display Figure 1 Schematic diagram of the microstructure in section C.
[0031] Figure 5 is a graph showing the relationship between aluminum fluoride concentration and radial compressive strength.
[0032] Figure 6 is a graph showing the relationship between aluminum fluoride concentration and radial compressive strength.
[0033] Figure 7 It is a graph showing the relationship between the volume ratio and the radial compressive strength.
[0034] Figure 8 It is a graph showing the relationship between the volume ratio and the radial compressive strength. DETAILED DESCRIPTION
[0035] Hereinafter, embodiments of the present invention will be described based on the drawings.
[0036] like Figure 1 As shown in FIG. 1 , the sintered bearing 1 of the present embodiment is formed of a cylindrical porous body having a bearing surface 1a on the inner periphery. When the shaft 2 is inserted into the inner periphery of the sintered bearing 1 and the shaft 2 is rotated in this state, the lubricating oil retained in the numerous pores of the sintered bearing 1 seeps out to the bearing surface 1a as the temperature rises. The seeping lubricating oil forms an oil film in the bearing gap between the outer peripheral surface of the shaft 2 and the bearing surface 1a, and the shaft 2 is supported by the bearing 1 in a relatively rotatable manner.
[0037] The sintered bearing 1 of the present embodiment is formed by filling a mold with raw material powders obtained by mixing various powders, compressing the raw material powders into a powder compact, sintering the powder compact, and then shaping and, if necessary, infiltrating lubricating oil into the compact.
[0038] The raw material powder of the present embodiment is a mixed powder obtained by mixing aluminum-copper alloy powder, phosphorus-copper alloy powder, graphite powder, and aluminum fluoride and calcium fluoride as sintering aids. The details of each powder are described below.
[0039] [Aluminum-Copper Alloy Powder]
[0040] As aluminum-copper alloy powder, aluminum-copper alloy powder obtained by pulverizing a complete alloy powder of copper and aluminum and adjusting the particle size is used. Specifically, 7 to 17% by mass of aluminum-copper alloy powder can be used, and preferably 8.5 to 12% by mass of aluminum-copper alloy powder can be used. Since alloyed powder is used, there are no operational problems caused by the scattering of aluminum single powder with a small specific gravity. The particle size of the aluminum-copper alloy powder is less than 100 μm, and the average particle size is about 35 μm.
[0041] The average particle size can be measured, for example, by a laser diffraction scattering method. In this measuring method, a laser is irradiated to a particle group, and a particle size distribution is calculated from an intensity distribution graph of diffracted / scattered light emitted by the laser, and the average particle size is further calculated. As a measuring device for the average particle size, for example, SALD-3100 from Shimadzu Corporation can be used.
[0042] The more aluminum there is in the aluminum-copper alloy powder, the higher the proportion of the β phase. The β phase undergoes a eutectic transformation at 565°C to become the α phase and the γ phase, so the more aluminum there is, the more γ phase is generated in the sintered body. Since the γ phase reduces the corrosion resistance to organic acids contained in engine oil, gasoline, light oil, etc. or ammonia contained in exhaust gas, it is not appropriate to increase the amount of aluminum excessively. On the other hand, when the aluminum content is too low, the advantages of aluminum bronze sintered bearings (especially wear resistance) cannot be obtained. Therefore, the aluminum content in the sintered bearing 1 is 3% to 13% by mass, preferably 8.5% to 12% by mass.
[0043] [Phosphorus alloy powder]
[0044] As the phosphorus alloy powder, phosphorus-copper alloy powder is used, for example, 7-10 mass% phosphorus-copper alloy powder. Phosphorus improves the wettability between the solid phase and the liquid phase during sintering, and has the effect of promoting the sintering of the aluminum-copper alloy during the sintering process. The phosphorus content in the sintered bearing is 0.05-0.6 mass%, preferably 0.1-0.4 mass%. When the phosphorus content is less than 0.05 mass%, the sintering promoting effect between the solid and liquid phases is lacking; when the phosphorus content is greater than 0.6 mass%, due to excessive sintering, the precipitation of the γ phase increases, and the sintered body becomes brittle.
[0045] [Graphite powder]
[0046] Graphite exists mainly in the form of free graphite dispersed in the pores of the blank, and gives the sintered bearing excellent lubricity, which helps to improve wear resistance. The mixing amount of graphite is 3 to 10% by mass (3 to 10 parts by mass) relative to the total of 100% by mass (100 parts by mass) of the aluminum-copper alloy powder and the phosphorus alloy powder, and is preferably 3 to 6% by mass (3 to 6 parts by mass). When aluminum is less than 3% by mass (3 parts by mass), the effect of improving lubricity and wear resistance obtained by adding graphite cannot be obtained. On the other hand, when it is greater than 10% by mass (10 parts by mass), the diffusion of aluminum into copper is hindered, resulting in reduced strength. By using granulated graphite powder as graphite powder, when adding 4% by mass (4 parts by mass) or more of graphite powder to the raw material powder, it is possible to prevent the deterioration of moldability. Granulated graphite powder is a material that is granulated with a resin binder and then crushed into fine powder of natural graphite or artificial graphite. As graphite powder, it is preferred to use a material with a particle size of 145 mesh or less.
[0047] [Aluminum fluoride]
[0048] When sintering aluminum-copper alloy powder, the aluminum oxide film formed on the surface of the particles will significantly hinder sintering. Aluminum fluoride (AlF3) powder melts at the sintering temperature of aluminum-copper alloy powder, i.e., 880°C to 1000°C, and slowly evaporates, protecting the surface of the aluminum-copper alloy powder and inhibiting the formation of aluminum oxide, thereby promoting sintering and increasing the diffusion of aluminum. Since aluminum fluoride evaporates and volatilizes during sintering, it hardly remains in the sintered body after sintering. The mixing ratio of aluminum fluoride in the raw material powder is preferably 0.05 to 0.3 mass % (0.05 to 0.3 mass parts) relative to the total 100 mass % (100 mass parts) of aluminum-copper alloy powder and phosphorus alloy powder. When the mixing amount of aluminum fluoride is less than 0.05 mass % (0.05 mass parts), it is difficult to inhibit the formation of aluminum oxide. When the mixing amount of aluminum fluoride exceeds 0.3 mass % (0.3 parts by mass), the effect of suppressing the formation of aluminum oxide is saturated (when 8.5 to 12 mass % of aluminum-copper alloy powder is used).
[0049] [Calcium fluoride]
[0050] Calcium fluoride (CaF2) acts like a catalyst in the presence of phosphorus, for example, as a sintering aid for aluminum fluoride, which helps to promote sintering. The mixing ratio of calcium fluoride is preferably about 0.01 to 0.2 mass % (0.01 to 0.2 parts by mass) relative to the total of 100 mass % of the aluminum-copper alloy powder and the phosphorus alloy powder. When the mixing amount of calcium fluoride is less than 0.01 mass % (0.01 parts by mass), it is difficult to obtain the effect as a sintering aid for aluminum fluoride. When the mixing amount of calcium fluoride is greater than 0.2 mass % (0.2 parts by mass), it will remain in the sintered body as calcium fluoride particles.
[0051] Next, a description will be given of a method for producing the sintered bearing 1. The sintered bearing 1 of the present embodiment is produced through a raw material powder preparation step, a powder pressing step, a sintering step, a shaping step, and an oil impregnation step.
[0052] [Raw material powder preparation step S1]
[0053] In the raw material powder preparation step S1, raw material powders of the sintered bearing 1 are prepared and generated. When generating the raw material powders, the respective powders are blended and mixed so as to obtain a sintered body containing 3 to 13 mass % of aluminum and 0.05 to 0.6 mass % of phosphorus, the remainder being mainly copper and carbon, and further containing inevitable impurities. For example, with respect to a total of 100 mass% (100 mass parts) of 90 to 97 mass% (90 to 97 mass parts) of the above-mentioned aluminum-copper alloy powder and 3 to 10 mass% (3 to 10 mass parts) of the above-mentioned phosphorus-copper alloy powder, a material to which 3 to 6 mass% (3 to 6 mass parts) of graphite powder, 0.05 to 0.3 mass% (0.05 to 0.3 mass parts) of aluminum fluoride, 0.01 to 0.2 mass% (0.01 to 0.2 mass parts) of calcium fluoride, and 0.1 to 1.0 mass% (0.1 to 1.0 mass parts) of zinc stearate, a lubricant for facilitating moldability, is added as a raw material powder.
[0054] [Powder pressing process]
[0055] In the powder pressing step, the raw material powder is compressed and molded to form a powder compact 1' ( Figure 3A , 3B ), the powder compact 1 ′ has a shape corresponding to the shape of the sintered bearing 1.
[0056] Specifically, for example, a molding die that divides a cavity that simulates the shape of a powder compact is placed in a CNC press machine driven by a servo motor, and the raw material powder filled in the cavity is compressed with a pressure of 200 to 700 MPa to form the powder compact 1'. When the powder compact 1' is formed, the molding die can be heated to above 70°C.
[0057] In the manufacturing method of the sintered bearing 1 described above, since aluminum-copper alloy powder is used as the aluminum source instead of aluminum powder, the operational problems caused by the scattering of aluminum particles with a small specific gravity can be avoided in the powder pressing process. In addition, since copper powder is not added, there is almost no uneven copper powder in the sintered body, and the occurrence of corrosion caused by this part is avoided. Therefore, the corrosion resistance of the sintered bearing 1 is improved.
[0058] [Sintering process]
[0059] In the sintering step, the powder compact is heated at a sintering temperature to form a sintered body by sintering adjacent raw material powders. Figure 2 A mesh belt continuous furnace 10 is shown.
[0060] The sintering furnace 10 has a configuration in which an input section 11, a preheating section 12, a heating section 13, and a cooling section 14 are sequentially arranged in a conveying direction (the direction indicated by the arrows in the extended line of the two-dot chain line in the figure). A mesh belt 15 as a conveying device is provided from the input section 11 as the entrance of the furnace 10 to the terminal of the cooling section 14 as the exit of the furnace 10. By driving the mesh belt 15 with a driving source 16, the powder compact is continuously conveyed in the direction of the arrow and sequentially passes through each section 11 to 14.
[0061] The preheating section 12 and the heating section 13 are provided with heat-releasing bodies 12a and 13a and supply ports 12b and 13b for supplying the atmosphere gas into the furnace, respectively. In the preheating section 12, the lubricant such as zinc stearate contained in the powder compact is removed by heating (dewaxing), and in the heating section 13, the preheated powder compact is sintered. Hydrogen, nitrogen or a mixed gas thereof is used as the atmosphere gas in the furnace 10. The sintering temperature is preferably in the range of 880 to 1000°C (preferably 920 to 980°C). In addition, the combined sintering time of the preheating section 12 and the heating section 13 is preferably about 10 to 60 minutes.
[0062] In this embodiment, the powder compact 1' is contained in a sealed container 20. The containers 20 are sequentially supplied to the mesh belt 15, and each container 20 is sequentially sent to each section 11 to 14 in the furnace 10, so that the powder compact in the container 20 is sintered. Figure 3A , Figure 3B As shown, for example, a tray with a lid having a tray 21 (also referred to as a plate) as a container body and a lid 22 can be used. Two or more powder compacts 1' are arranged on the tray 21, and then the lid 22 is fitted into the upper surface opening of the tray 21, thereby forming a closed space 23 isolated from the external atmosphere inside the tray 20 with a lid. The sintering process in this embodiment is performed by accommodating the powder compact 1' in the closed space 23 inside the container 20 in this way. It should be noted that the tray 21 and the lid 22 can be formed of stainless steel, for example.
[0063] During the temperature rise accompanying sintering, an aluminum oxide (Al2O3) film is formed on the surface of the aluminum-copper alloy particles. Since the aluminum oxide film hinders sintering, insufficient sintering (insufficient neck strength) will occur if it is left in this state. Aluminum fluoride added as a countermeasure vaporizes (sublimates) from around 600°C and reacts with the aluminum oxide film to generate a gas phase of AlOF according to the following reaction formula.
[0064] Al2O3(s)+AlF3(g)=3AlOF(g)
[0065] The aluminum oxide film is destroyed and removed by this reaction. As a result, the sintering between adjacent aluminum-copper alloy structures proceeds smoothly, the neck strength between the structures increases, and a high-strength sintered body is obtained.
[0066] [Shaping process]
[0067] In the shaping process, the sintered body, which has expanded compared to the powder compact 1' due to sintering, is compressed in the axial and radial directions and shaped. Through shaping, the pores on the surface of the expanded sintered body are crushed, and a density difference is generated between the core and the surface. Therefore, after shaping, Figure 1 As shown, the surface portion (hatched area) of the sintered bearing 1 becomes a compression layer, and the density of the compression layer Po of the surface portion on the outer diameter surface 1b side and the density of the compression layer Pi of the surface portion on the bearing surface 1a side are both higher than the density of the core portion 1c.
[0068] [Oil-containing process]
[0069] The oil-containing process is a process of infiltrating lubricating oil into the product 1 (sintered bearing). Product 1 is placed in the tank of the oil-containing device, and then the lubricating oil is injected into the tank. Next, the lubricating oil is infiltrated into the pores of the product 1 by reducing the pressure in the tank. As a result, since the lubricating oil is maintained in each pore of the porous sintered bearing, a good lubrication state can be obtained from the start of operation. As the lubricating oil, mineral oil, polyalphaolefin (PAO), ester, liquid grease, etc. can be used. Among them, the oil-containing process can be implemented according to the use of the bearing, and the oil-containing process can also be omitted according to the use.
[0070] After the above process, the Figure 1 The sintered bearing 1 shown has a structure obtained by sintering an aluminum-copper alloy, contains 3-13 mass % of aluminum and 0.05-0.6 mass % of phosphorus, and the remainder is mainly composed of copper and carbon and contains inevitable impurities.
[0071] The sintered bearing 1 has Figure 4A , Figure 4B , Figure 4C The microstructure schematically shown in FIG. Figure 4A for Figure 1 The enlarged view of part A, Figure 4B for Figure 1 The enlarged view of part B, Figure 4C for Figure 1 An enlarged view of section C.
[0072] Figure 4A to Figure 4CIn the figure, the hatched area 3 is an aluminum-copper alloy structure. Since the aluminum-copper structure 3 is a complete alloy structure, the ratio (weight ratio) of copper to aluminum is constant in any part of the aluminum-copper structure 3. In the aluminum-copper alloy structure 3, an aluminum oxide film 4 is present around the surface in contact with the external atmosphere and the internal pores d1 communicating with the external atmosphere. Therefore, corrosion resistance and wear resistance are imparted to the sintered bearing 1. Since free graphite 5 is distributed in the internal pores d1 and the surface pores d2, lubricity and wear resistance can be obtained.
[0073] In addition, in the present embodiment, since copper powder is not added to the raw material powder, there is almost no uneven copper powder in the sintered body, which avoids the occurrence of corrosion caused by this part. Although the illustration is omitted, phosphorus exists in the grain boundaries of the adjacent aluminum-copper alloy structure 3. Phosphorus improves the wettability between the solid phase and the liquid phase during sintering, so the bonding strength between the particles is improved, which can increase the strength of the sintered body. Aluminum fluoride will evaporate and volatilize completely during sintering, so it will hardly remain in the sintered body, but calcium fluoride will sometimes remain in the sintered body. The calcium fluoride remaining in the sintered body can act as a solid lubricant.
[0074] In the above-described embodiment, although copper powder is not added to the raw material powder, copper powder can also be added as needed. In this case, in addition to aluminum-copper alloy structure, phosphorus-copper alloy structure, aluminum-phosphorus-copper alloy structure and graphite structure, a copper structure is also formed in the sintered body. The sintered body of the present embodiment is a sintered body containing aluminum and phosphorus, and the main component of the remainder is copper, but in the "remainder" mentioned here, other elements other than Cu can be added to the limit of not damaging the necessary corrosion resistance and mechanical strength. As an example of other elements, any one of Si, Sn, Ni, Zn, Fe, Mn, etc., or more than two kinds can be cited. Among them, the content of the above-mentioned other elements in the sintered body is each lower than the content of copper and aluminum. In addition, depending on the sintering conditions, sometimes a trace amount of calcium fluoride that is not completely evaporated will remain in the sintered body, but the content of F and Ca in the sintered body in this case is also lower than the content of copper and aluminum.
[0075] As described above, when the aluminum bronze sintered bearing 1 is made compact, it is known that the strength of the sintered body is often lower than expected. Various test results show that this phenomenon is caused by the following reason: aluminum fluoride does not fully function as a sintering aid.
[0076] In the closed space 23 in the container 20, as described above, the aluminum fluoride vaporized during sintering reacts with aluminum oxide to generate AlOF gas. As the sintered bearing 1 is compacted, the number of powder compacts contained in the container 20 is the same as before compaction, and as a result, the residual volume of the closed space 23 (the value of the volume of the closed space 23 minus the total volume of the powder compact 1') increases relatively. As a result, since the concentration of vaporized aluminum fluoride (the concentration of AlOF gas) decreases, the reaction between aluminum fluoride and aluminum oxide cannot be fully carried out, and aluminum oxide remains at the grain boundaries. Therefore, the progress of sintering is impaired, and the strength of the sintered body decreases.
[0077] Based on the above inspection results, in the present embodiment, the powder compact 1' is sintered in the closed space 23 isolated from the outside atmosphere, and the concentration (expected concentration) of the aluminum fluoride gas is managed and sintered when it is assumed that all the aluminum fluoride contained in the raw material powder is vaporized in the closed space 23. The concentration is calculated from the residual volume of the closed space 23 (the value obtained by subtracting the total volume of the powder compact 1' from the volume of the closed space 23) when a predetermined number (the number of powder compacts arranged in the tray in the actual sintering process) of the powder compacts 1' are arranged in the tray 20, and the total amount of aluminum fluoride present in the closed space 23. The "concentration management" in the present embodiment includes determining the total amount of aluminum fluoride in the closed space 23 (the content of aluminum fluoride in each powder compact 1') in consideration of the above residual volume, or determining the volume of the closed space 23 in consideration of the total amount of aluminum fluoride in the closed space 23. That is, “control of concentration” means that one of the remaining volume of the closed space 23 and the amount of aluminum fluoride in the closed space 23 is taken into consideration and the other is determined.
[0078] Figure 5 The results of the radial compressive strength (defined in JIS Z2507) of the sintered bodies sintered under the above-mentioned conditions of different aluminum fluoride concentrations are shown. The sintering temperature of the test piece (sintered body) was 950°C, and the size of the test piece was an inner diameter of approximately Approximate outer diameter The length is approximately 6 mm. The volume of the test piece is 0.2971 cm 3 , the mass is 1.72~1.82g.
[0079] from Figure 5It can be understood from the results shown that the higher the concentration of aluminum fluoride, the higher the radial compressive strength of the sintered body. Therefore, it is preferred to increase the concentration of aluminum fluoride as much as possible. In order to increase the concentration of aluminum fluoride, it is necessary to increase the content of aluminum fluoride or reduce the volume of the enclosed space. In the former case (increasing the content of aluminum fluoride), it is necessary to change the mixing amount of aluminum fluoride according to the product size. Since each product size requires a different mixing amount of material, management becomes difficult. Therefore, in order to increase the concentration of aluminum fluoride, reducing the volume of the enclosed space 23 is a more realistic response. From the perspective of ensuring productivity, etc., the reduction in the volume of the enclosed space 23 is preferably achieved by reducing the height dimension H of the enclosed space 23 (refer to Figure 3B ) to achieve it.
[0080] Figure 6 The following shows the measurement results of radial compressive strength when the same test as above was conducted with the sintering temperature of the sintered body being changed.
[0081] Figure 6 The results shown show that the radial compressive strength of the sintered body increases as the sintering temperature increases, and that even at a sintering temperature of 940°C, which is close to low temperature, if the concentration of aluminum fluoride in the closed space 23 (expected concentration) is 5.0 ppm or more, a radial compressive strength of 200 MPa or more can be ensured. It can also be understood that if the concentration of aluminum fluoride is increased, a radial compressive strength of 250 MPa or more, and further 300 MPa or more can be obtained. Here, as the minimum necessary strength in many uses of the sintered bearing 1, a radial compressive strength of 200 MPa is required in many cases. Therefore, in order to ensure the minimum radial compressive strength even at low temperature sintering, the concentration of aluminum fluoride is set to a value of 5.0 ppm or more, preferably 10 ppm or more, and more preferably 15 ppm or more. The upper limit of the concentration of aluminum fluoride is below the saturation concentration in the closed space 23.
[0082] The hardness of the test piece used in the above test was measured, and the result was that the Rockwell hardness HRF was 30 or more (substantially 40 or more) and 110 or less (substantially 100 or less, more substantially 90 or less, and further substantially 70 or less), confirming that the sintered body also had sufficient hardness. In addition, the density of the test piece was measured and the result was confirmed to be 5.6 g / cm 3 Above, 6.2g / cm 3 The following density.
[0083] By sintering under the above conditions, such as Figure 4A , Figure 4B , Figure 4CAs shown, the aluminum oxide film 4 is surely removed from the grain boundary of the aluminum-copper alloy structure 3 adjacent to the core 1c, and the aluminum oxide film 4 no longer exists in the grain boundary. Therefore, the sintering between the aluminum-copper alloy structures 3 can be fully carried out, the neck strength between the aluminum-copper alloy structures 3 can be improved, and the strength of the sintered body can be stably improved.
[0084] Next, the radial compressive strength of the powder compact was measured by changing the ratio of the total volume of the powder compact to the volume of the closed space 23 (the volume when the powder compact is not contained) (hereinafter simply referred to as "volume ratio") when sintering was performed. Figure 7 and Figure 8 The test piece used in the above test was used. Figure 7 The radial compressive strength of the test piece when the sintering temperature is set to 950°C is shown. Figure 8 The radial compressive strengths of the test pieces in three cases where the sintering temperatures were set at 940°C, 950°C, and 960°C were compared.
[0085] from Figure 7 and Figure 8 It can be understood that the greater the volume ratio, the greater the radial compressive strength. If the volume ratio is 5.0% or more, a radial compressive strength of at least 200 MPa can be obtained. Therefore, the volume ratio is preferably set to 5% or more (preferably 10% or more, more preferably 15% or more).
[0086] The aluminum bronze sintered bearing 1 of this embodiment can have both high corrosion resistance and mechanical strength even at high temperatures. The sintered bearing 1 can be widely used for applications requiring these characteristics. Therefore, it can be used as an accessory that is arranged close to an automobile engine. Specifically, it can be used as a sintered bearing for a fuel pump that requires corrosion resistance to organic acid corrosion or sulfidation corrosion when in contact with gasoline or light oil, a sintered bearing for an exhaust gas circulation device (EGR) that requires corrosion resistance to exhaust gas or engine oil at high temperatures, or a sintered bearing for a turbocharger. In addition, it can also be used as a bearing for a fishing reel, for example, a fishing tackle.
[0087] In addition, in the above description, the sintered bearing 1 is exemplified as being suitable for a perfect circular bearing in which the bearing surface 1a is set to a perfect circle, but it is not limited to a perfect circular bearing, and can also be used as a fluid dynamic pressure bearing in which a dynamic pressure generating portion such as a herringbone groove or a spiral groove is set on the outer peripheral surface of the bearing surface 1a or the shaft 2.
[0088] It should be noted that, in the above embodiment, the case of using a continuous sintering furnace 10 is illustrated, but a batch sintering furnace can also be used instead. In addition, a closed space closed by a shutter or the like can be formed in the furnace, and the container 20 is not used in the closed space, but the powder compact 1' is directly put into the closed space. At this time, by managing the concentration of aluminum fluoride in the closed space, the same effect as above can be obtained. In this case, the aluminum fluoride gas can be supplied from outside the furnace into the closed space while managing its concentration.
[0089] Explanation of symbols
[0090] 1 Sintered bearings
[0091] 1a Bearing surface
[0092] 1c Core
[0093] 1' Powder compact
[0094] 2 Axis
[0095] 3 Aluminum-Copper Alloy Structure
[0096] 4 Alumina coating
[0097] 5. Graphite
[0098] 10 Sintering furnace
[0099] 20 containers (trays with lids)
[0100] 21 Pallets
[0101] 22 Cover
[0102] 23 Enclosed Space
Claims
1. A method for manufacturing a sintered bearing, wherein the sintered bearing is formed by sintering a raw material powder containing aluminum fluoride, has a structure obtained by sintering an aluminum-copper alloy, contains 3 to 13% by mass of aluminum and 0.05 to 0.6% by mass of phosphorus, and the remainder is copper and carbon, and contains inevitable impurities, The method for manufacturing a sintered bearing is characterized in that: The raw material powder contains 0.05 mass % to 0.3 mass % of the aluminum fluoride, The sintering is performed in a closed space, and the sintering is performed while controlling the concentration of the aluminum fluoride gas when it is assumed that all the aluminum fluoride contained in the raw material powder is vaporized in the closed space. The sintering is performed by placing two or more powder compacts in the closed space so that the ratio of the total volume of the two or more powder compacts to the volume of the closed space is 5% or more.
2. The method for manufacturing a sintered bearing according to claim 1, wherein: The closed space is formed by a container body capable of accommodating two or more powder compacts and a cover detachable from the container body.
Citation Information
Patent Citations
Sintered bearing and manufacturing method for same
WO2013137347A1
Sintered bearing and manufacturing method for same
CN104204247A
Sintered bearing for fuel pump and method for manufacturing same
CN105473258A
Sintered bearing for an egr valve and manufacturing method thereof
CN105517735A
Sintering assistant, aluminum-containing copper-based alloy powder to be sintered, and sintered compact formed by sintering the aluminum-containing copper-based alloy powder
JP2009114486A